Clinical profile of neonates with polycythemia at a tertiary care hospital in North East, India - Beti, Punyo; Singh, C. Shyamsunder; Smilie, Chabungbam; Rama, Bharghav (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal polycythemia (NPC) is associated with hyper viscosity of blood causing impairment of tissue oxygenation, perfusion and formation of microthrombi. Polycythemia is defined as a venous hematocrit (Hct) of≥65% or a haemoglobin (Hb)>22g/dl. It presents with a nonspecific clinical features like plethora, poor feeding, lethargy, hypoglycaemia, jaundice. The aim of this study was to assess the clinical profile in neonates with polycythemia admitted in the paediatrics ward of a tertiary care centre in North East, India. Methods: A hospital based cross sectional study was carried out from January 2021 to October 2022 and 149 participants were recruited after fulfilling the inclusion and exclusion criteria with approval from ethical board. Statistical analysis was done using SPSS statistics version 21.0 WINDOWS (IBM Corp. Armonk, NY, USA). Results: Among the 149 cases, 89 (59.7%) neonates were symptomatic and 60 (40%) neonates were asymptomatic. The most common presentation were poor feeding and plethora in 89 neonates each (59.7% each), followed by lethargy (39.6%), hypogycemia (30.2%), jaundice (29.5%), necrotizing enterocolitis (21.5%), cyanosis (10%) and oliguria (10%). Partial exchange therapy was done in 30 neonates (20%), 59 neonates (39.6%) required intravenous fluid and 60 neonates (40.3%) were treated conservatively. All neonates were successfully discharged and no deaths were noted in our study. Conclusions: Anticipation, early recognition and intervention can prevent acute short-term complications and long-term sequelae of this easy to treat disorder.